1994
DOI: 10.1021/jm00042a014
|View full text |Cite
|
Sign up to set email alerts
|

Maleimidoethyl 3-(Tri-n-butylstannyl)hippurate: A Useful Radioiodination Reagent for Protein Radiopharmaceuticals To Enhance Target Selective Radioactivity Localization

Abstract: In pursuit of radiolabeled monoclonal antibodies (mAbs) with rapid urinary excretion of radioactivity from nontarget tissues, radioiodinated mAbs releasing a m-iodohippuric acid from the mAbs in nontarget tissues were designed. A novel reagent, maleimidoethyl 3-(tri-n-butylstannyl)hippurate (MIH), was synthesized by reacting N-(hydroxyethyl)maleimide with N-Boc-glycine before coupling with N-succinimidyl 3-(tri-n-butylstannyl)benzoate (ATE). MIH possessed a maleimide group for mAb conjugation and a butylstanny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 8 publications
(16 reference statements)
0
52
0
Order By: Relevance
“…No significant decrease in the radioactivity level in the tumor was observed with [ 125 I]-SIB-OST7 (IgG) between the postinjection intervals. In our previous study using NGA, although [ 131 I]SIB-NGA was eliminated from murine liver more slowly than [ 131 I]-MIH-NGA, the former registered residual radioactivity levels in the liver similar to the latter at 24 h postinjection (19). In addition, radiolabeled OST7 (IgG) via direct radioiodination (26,42), via [ 67 Ga]succinyldeferoxamine with an ester bond (8), and via [ 111 In]-cDTPA (43) indicated unchanged radioactivity levels in the same tumor model (KT005) during the same postinjection intervals.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…No significant decrease in the radioactivity level in the tumor was observed with [ 125 I]-SIB-OST7 (IgG) between the postinjection intervals. In our previous study using NGA, although [ 131 I]SIB-NGA was eliminated from murine liver more slowly than [ 131 I]-MIH-NGA, the former registered residual radioactivity levels in the liver similar to the latter at 24 h postinjection (19). In addition, radiolabeled OST7 (IgG) via direct radioiodination (26,42), via [ 67 Ga]succinyldeferoxamine with an ester bond (8), and via [ 111 In]-cDTPA (43) indicated unchanged radioactivity levels in the same tumor model (KT005) during the same postinjection intervals.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, we developed a novel radioiodination reagent with an ester bond to liberate m-iodohippuric acid, maleimidoethyl 3-(tri-n-butylstannyl)hippurate (MIH) (19). Preliminary studies using galactosylneoglycoalbumin (NGA) as a model protein indicated that MIH liberates m-iodohippuric acid as the major radiometabolite after lysosomal proteolysis in hepatic parenchymal cells, and the metabolite was excreted rapidly from the hepatocytes into the urine intact.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-iodohippuric acid was selected to conjugate Fab fragment because it was excreted through the urinary system rapidly and it resisted in vivo deiodination. 41,42 Their findings indicated that HML was able to reduce renal activity levels without sacrificing the target activity accumulation capacity. 43 The radiolabeled peptide, 111 In-DTPA-D-Phe 1 -Octreotide, has been used clinically to visualize somatostatin receptor-positive tumors.…”
Section: Discussionmentioning
confidence: 99%
“…125 I]SIB-c(RGDfK) (6) N-Succinimidyl ester of 3-(tri-n-butylstannyl) benzoate (ATE) (0.5 mg), which was synthesized using a method reported previously with a slight modification from 3-broobenzoic acid via a fourstep, 18,29) was dissolved in 79 µL of ethanol. Fifteen microliter of chloramine-T (1 mg/mL) in ethanol, 21 µL of 1% acetic acid in ethanol, and […”
Section: Preparation Of [mentioning
confidence: 99%